Daily Saturated Fat and Sodium Content of Elementary School Meals in a Large Sample of 128 Geographically Diverse School Systems in the United States. (14th June 2022) - Richardson, Scott; Cohen, Juliana; Rimm, Eric; Gortmaker, Steven
Abstract: Objectives: Subsidized meals provided through the National School Breakfast and Lunch programs are an important source of daily nutrition for approximately 30 million school-aged students across the United States. Despite federal regulations limiting saturated fat and sodium levels on a weekly average basis, daily nutrient content of these meals is not regulated, leading to potential large fluctuations and intake well in excess of dietary recommendations. The objective of this study was to assess the daily prevalence of potential school meal combinations that exceed the USDA's weekly average reimbursable meal thresholds for saturated fat and sodium in U.S. elementary schools. Methods: Four weeks of publicly available school breakfast and lunch menus with associated nutrition data were collected from a stratified random sample of 128 school districts to inform an imputed dataset of all possible daily reimbursable meal offerings. Daily distributions of total meal sodium and saturated fat content were then compared against weekly average USDA nutrient thresholds to assess the national prevalence of daily meals in excess of school meal guidelines. Results: Most sample districts' menus (97.7% for breakfast, 100.0% for lunch) contained reimbursable meal combinations on a daily basis that exceed USDA weekly average dietary guideline thresholds for saturated fat and/or sodium. Conclusions: Widespread availability of meals exceeding average sodium and saturated fat guidelines suggest that concern about child overnutrition through school meals is warranted. Daily entrée saturated fat and sodium caps should be considered to limit prevalence of meal combinations that well exceed current guidelines. Funding Sources: T32 HL098048/HL/NHLBI NIH HHS/United States.